Supply Chain Management in Pandemic Times : An Experience from Macedonian Automotive Industry - Kochov, Atanas (Array, 2021)
The automotive industry is one of the sectors that has been hardest hit by the pandemic crisis. The pandemic"s effects have resulted in multiple disorders, which led to loss of important suppliers and the inability to obtain vital parts, exposing the vulnerability of current Lean Just in Time supply chains. This paper provides a brief analysis of the COVID-19 pandemic's impact on the automotive sector in the Republic of North Macedonia. The provided findings are based on a research study conducted simultaneously in eight automotive organizations in the Republic of North Macedonia. This study sought to investigate the extent of the pandemic's influence on organizations' supply chains, what preventive steps have been implemented to minimize the virus's transmission, and what are the most prevalent obstacles that organizations have experienced during the pandemic.